Ammonia-responsive thermoplastic starch films incorporated with gallic acid-cobalt metal-organic frameworks (GA/Co-MOF) for real-time tracking of shrimp freshness - Yilmaz, Mustafa Tahsin; Parlak, Mahmut Ekrem; Uzuner, Kubra; Yildiz, Zehra Irem; Dundar, Ayse Neslihan; Sahin, Oya Irmak; Saricaoglu, Furkan Turker (Elsevier, 2026)
Developing ammonia-responsive biopolymer-based smart films with strong mechanical properties and reliable visual freshness indicators is a significant research focus. Integrating cobalt-based metal-organic frameworks (CoMOF) into a polymer matrix is a contemporary method for manufacturing intelligent packaging materials, primarily due to their rapid responsiveness to ammonia. This study successfully synthesized an ammonia-sensitive Co-MOF by using gallic acid as the ligand (GA/Co-MOF) and integrated them into a thermoplastic starch (TPS) matrix, creating high-performance, multifunctional TPS-based intelligent active composite films (TPS/Co-MOF). FTIR analysis indicates that cobalt exhibits a strong affinity for the carboxy and hydroxy groups of gallic acid, leading to the formation of spherical aggregates, which have diameters of between 600 and 1000 nm, as visualized using SEM. A thorough analysis assessed the impact of GA/Co-MOF on the films' physicochemical, water barrier, and morphological properties, as well as their color, optical, UV-blocking, and material characteristics (thermal, crystallographic, molecular, and mechanical) and ammonia-responsive performances. The GA/Co-MOF nanofillers were uniformly dispersed in the TPS matrix, significantly enhancing tensile strength (from 4.35 to 5.29 MPa), elongation at break (from 122.97 to 153.7 %), puncture force (from 612.78 to 1069.96 g), puncture deformation (from 3.78 to 4.87 mm), water resistance, and UV-blocking abilities. Additionally, the films exhibited improved thermal stability, toughness, elasticity, and ammonia-sensitive discoloration properties. Notably, the TPS/Co-MOF films enabled effective real-time visual monitoring of shrimp freshness, with a faster color response time than existing nanocomposite films, making them promising for active and intelligent food packaging. These findings highlight the significant potential of TPS/Co-MOF films to meet the demands of safe packaging solutions with superior mechanical performance and freshness monitoring.
Keywords: Smart packaging; Thermoplastic starch; Metal-organic framework; Ammonia sensitive; Material characterization